Evaluation of genotoxicity and subchronic toxicity of the standardized leaves infusion extract of Copaifera malmei Harms in experimental models. (30th January 2018) - Pavan, Eduarda; Damazo, Amilcar Sabino; Lemos, Larissa Maria Scalon; Adzu, Bulus; Balogun, Sikiru Olaitan; Arunachalam, Karuppusamy; Martins, Domingos Tabajara de Oliveira
Abstract: Ethnopharmacological relevance: Copaifera malmei Harms (Fabaceae), known mainly as óleo-mirim, is a native and endemic plant found in the states of Mato Grosso and Goiás of Brazil. The plant's leaves infusion is popularly used by riverine communities of the northern Araguaia microregion, Mato Grosso, Brazil, for the treatment of gastric ulcers and inflammatory diseases of the respiratory tract. The gastric antiulcer activity of the standardized leaves infusion extract of Copaifera malmei (SIECm) in rodents has been reported. The objective of this study was to advance the investigation of the safety profile of SIECm by evaluating the genotoxicity and subchronic toxicity using in vitro and in vivo experimental models. Materials and methods: SIECm was prepared by infusion, by incubating the powdered dried leaves material in boiled water for 15 min. In vitro genotoxicity of SIECm (10, 30 or 100 μg/mL) was assessed by micronucleus and comet tests using Chinese hamster ovary (CHO-k1) epithelial cells. The evaluation of subchronic toxicity profile was performed by daily oral administration of SIECm (100, 400 or 1000 mg/kg) to Wistar rats for 30 days. Clinical observations of toxicological related parameters were done every 6 days. After the treatment period, blood was collected for hematological and biochemical analysis, and some organs were removed for macroscopic and histopathological analysis. Results: In the micronucleus assay, SIECm demonstrated anti-mutagenic activity. In the comet assay, SIECm presented anti-genotoxic effect preventing DNA damage at all the three concentrations tested with pre-treatment, while the same effect was only observed in the co-treatment at the lowest concentration. Post-treatment with SIECm increased the genetic damage induced by hydrogen peroxide (H2 O2 ) at the highest concentration. In the subchronic toxicity test, few changes were observed, such as increase in feed consumption in the group of animals treated with 100 mg/kg of the SIECm, which reversed after 6 days. There were no macroscopic, histological and relative weights changes in the organs of animals treated with SIECm. No toxicologically relevant changes were observed in the hematological analysis. Subchronic administration of SIECm reduced levels of alanine aminotransferase (ALT) and aspartate aminotransferase (AST) in animals treated with 100 mg/kg and serum triglyceride levels at 400 and 1000 mg/kg. However, the hematological and biochemical changes observed are within the physiological ranges for this animal species. Conclusion: The results demonstrate that SIECm is not genotoxic, and does not present toxicity when used orally for up to 30 days. In addition, it showed protection to the genetic damage induced by H2 O2. The SIECm therefore has a high safety margin for therapeutic use. Graphical abstract: